STUDI KOMPARATIF RESISTENSI ANTARA SAPI BALI DAN MADURA TERHADAP INFEKSI Fasciola gigantica - Ening Wiedosari (Pusbindiklat - LIPI, 2010)
Designing of future approaches for the control of Fasciola gigantica infection in cattle requires an understanding of the host-parasite relationships. This study was therefore undertaken to compare the susceptibility to infection with F. gigantica between Bali and Madura cattle. Seven Bali and seven Madura cattle were infected orally with 15 metacercariae of F. gigantica twice weekly for 32 weeks. Similar observations were made on four Bali and 4 Madura cattle maintained fluke-free as controls. The study shows that there was a trend of a lower fluke burden and faecal egg counts Madura cattle than in Bali cattle. The packed cell volume (PCV) values was significantlyhigher in infected Madura than in Bali cattle (P<0,05). The increased of eosinophil cell response and the antibody isotypes imunoglobulin (Ig)G1 in Madura cattle were significantly higher than in Bali cattle (P<0,05). These varying responses represent differences in host-parasite relationships between Bali and Madura cattle and may be linked to the observed varying levels of resistance to F. gigantica infection between these host.